867 Prognostic accuracy of triage tools for adults with suspected COVID-19 in a pre-hospital setting: an observational cohort study. Issue 3 (21st February 2022) - Marincowitz, Carl; Sutton, Laura; Stone, Tony; Campbell, Richard; Pilberry, Richard; Thomas, Benjamin; Goodacre, Steve
Abstract : Aims/Objectives/Background: Emergency Medical Service (EMS) and other practitioners assessing patients with suspected COVID-19 in the community must rapidly determine whether patients need treatment in hospital or can self-care. Tools to triage patient acuity have only been validated in hospital populations. We aimed to estimate the accuracy of five risk-stratification tools recommended to predict severe illness and compare accuracy to existing clinical decision-making in a pre-hospital setting. Methods/Design: An observational cohort study using linked ambulance service data for patients assessed by EMS crews in the Yorkshire and Humber region of England between 18th March 2020 and 29th June 2020 was conducted to assess performance of the PRIEST tool, NEWS2, the WHO algorithm, CRB-65 and PMEWS in patients with suspected COVID-19 infection. The primary outcome was death or need for organ support. Results/Conclusions: Of 7550 patients in our cohort, 17.6% (95% CI:16.8% to 18.5%) experienced the primary outcome. The NEWS2, PMEWS, PRIEST tool and WHO algorithm identified patients at risk of adverse outcomes with a high sensitivity (>0.95) and specificity ranging between 0.3 (NEWS2) and 0.41 (PRIEST tool). The high sensitivity of NEWS2 and PMEWS was achieved by using lower thresholds than previously recommended (NEWS2; 0–1 vs 2+ and PMEWS; 0–2 vs 3+). On index (first) assessment, 65% of patients were transported to hospital and EMS decision to transfer patients achieved a sensitivity of 0.84 (95% CI 0.83 to 0.85) and specificity of 0.39 (95% CI 0.39 to 0.40) to the primary outcome. This does not account for clinical reasons not to convey patients to hospital who subsequently deteriorated. Use of NEWS2, PMEWS, PRIEST tool and WHO algorithm could therefore potentially improve EMS triage of patients with suspected COVID-19 infection. Use of the PRIEST tool could significantly increase the sensitivity of triage without increasing the number of patients conveyed to hospital.